FogHA: An efficient handover authentication for mobile devices in fog computing. Issue 108 (September 2021) - Guo, Yimin; Guo, Yajun
Abstract: Fog computing is a new distributed computing paradigm that extends cloud services to the edge of the network, with features such as mobile support, location awareness, and low latency. Identity authentication in fog computing should support user mobility. For this reason, this paper proposes an anonymous handover authentication scheme for fog computing, FogHA, which achieves mutual authentication and key agreement between the adjacent fog node and the mobile device. FogHA only uses lightweight cryptographic primitives and eliminates redundant authentication messages with the cooperation of fog nodes, so it has high handover efficiency. The security of FogHA is proved by employing the formal security analysis under the Real-Or-Random (ROR) model. The informal security analysis shows that FogHA can resist known attacks. In addition, the comparison of communication and computation costs along with functionality features shows that the FogHA outperforms other existing schemes of the same type.